2019
DOI: 10.18552/ijpblhsc.v7i1.510
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Occupation-Centered Intervention Assessment for Occupational Therapy Level I Fieldwork

Abstract: This study examined the utility of the Occupation-Centered Intervention Assessment (OCIA) among occupational therapy students and their perceptions of the use of an occupation-centered approach to design interventions during level I fieldwork. Twenty-five students completed training on the OCIA, used the tool on level 1 fieldwork, and then completed a post-test survey containing closed and open-ended questions. Content analysis was used to analyze open-ended questions. Descriptive statistics was used to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Aligning with preliminary results from prior studies regarding utility in academic and fieldwork settings (Frigo et al, 2019;Jewell, Phillips, et al, 2020), novice fieldwork students tend to prefer rules and structure to guide decision-making rather than depending on observation-based analysis thus may find the OCIA beneficial during initial experiences within clinical practice (Copley et al, 2010). This study of the OCIA was conducted in Anchorage, Alaska, and was limited to participants within the state.…”
Section: Occupation-centered Intervention Assessmentmentioning
confidence: 64%
See 2 more Smart Citations
“…Aligning with preliminary results from prior studies regarding utility in academic and fieldwork settings (Frigo et al, 2019;Jewell, Phillips, et al, 2020), novice fieldwork students tend to prefer rules and structure to guide decision-making rather than depending on observation-based analysis thus may find the OCIA beneficial during initial experiences within clinical practice (Copley et al, 2010). This study of the OCIA was conducted in Anchorage, Alaska, and was limited to participants within the state.…”
Section: Occupation-centered Intervention Assessmentmentioning
confidence: 64%
“…Current literature indicates a gap between students' academic knowledge and clinical experience during Level II fieldwork regarding occupation-centered practice (Frigo et al, 2019;Copley et al, 2010). Evidence from this study suggested FWEs may not use an occupation-centered perspective to develop interventions.…”
Section: Implications For Occupational Therapy Educationmentioning
confidence: 75%
See 1 more Smart Citation
“…Nine research studies described qualitative methodologies including exploratory, phenomenological, and social constructionist perspectives. Two used a quantitative research framework consisting of an exploratory survey (Ashby & Chandler, 2010) and a post-test survey following a training event in which descriptive statistics were used to analyse closed-ended questions (Frigo et al, 2019). Interviews were most frequently used to collect data.…”
Section: Resultsmentioning
confidence: 99%
“…• Occupation-based practice (Dancza & Rodger, 2018;Di Tommaso et al, 2019;Raiz, 2007;Towns & Ashby, 2014;Vermaak & Nel, 2016), • Occupation-centred practice (Copley et al, 2011;Dancza & Rodger, 2018;Hanson, 2013b;Kaelin & Dancza, 2019), • Occupation-focused practice (Dancza & Rodger, 2018;Towns & Ashby, 2014) occupation-centred (Bergner, 2018;Copley et al, 2011;Copley et al, 2010;Frigo et al, 2019;Hanson, 2013b) • Occupation-based approaches (Di Tommaso et al, 2019;Hanson, 2013b).…”
Section: Terms Which Incorporated Occupation and Theorymentioning
confidence: 99%